Systemic risk: A new trade-off for monetary policy? - Stefan Laséen; Andrea Pescatori; Jarkko Turunen (Sveriges Riksbank, 2017)
We introduce time-varying systemic risk (à la He and Krishnamurthy, 2014) in an otherwise standard New-Keynesian model to study whether simple leaning-against-the-wind interest rate rules can reduce systemic risk and improve welfare. We find that while financial sector leverage contains additional information about the state of the economy that is not captured in in.ation and output leaning against financial variables can only marginally improve welfare because rules are detrimental in the presence of falling asset prices. An optimal macroprudential policy, similar to a countercyclical capital requirement, can eliminate systemic risk raising welfare by about 1.5%. Also, a surprise monetary policy tightening does not necessarily reduce systemic risk, especially during bad times. Finally, a volatility paradox a la Brunnermeier and Sannikov (2014) arises when monetary policy tries to excessively stabilize output.
Keywords: E3; E52; E58; E44; E61; G2; G12; 330; Monetary Policy; Endogenous Financial Risk; DSGE models; Non-Linear Dynamics; Policy Evaluation